Reducción de la captura secundaria y los descartes en la pesquería costera de pequeña escala del Algarve utilizando una red de trasmallo de monofilamento equipada con una red de protección - Szynaka, Monika (2019)
Experimental fishing was conducted off the port of Quarteira (southern Portugal) from October 2016 to February 2017 using standard trammel nets and modified nets rigged with a guarding net. The commercial catches of trammel nets rigged with a guarding net were 46.1% and 38.0% less than those of the standard net in numbers and economic value. However, there were significantly fewer commercial discards in biomass in the modified trammel nets (68.2%) and by-catch abundance and biomass were also lower in the modified nets (41.8% and 17.3% less, respectively). For the two main fish by-catch species, the modified net caught 62.2% fewer longfin gurnards (C. obscurus) and 33.1% fewer greater weever (T. draco) than the standard nets. Timing the removal from the nets of the main by-catch and discards species revealed savings in time associated with the use of modified nets. However, net damage occurred twice as much as in the modified net, probably contributing to the reduced commercial catches. The results indicate that trammel nets with the guarding net reduce by-catch and discards and save time, but are unlikely to be adopted by fishers targeting soles due to the higher costs of the modified nets and losses in commercial catches and earnings.